Legal supervision of audit practice in corporate takeovers - Kai, Liu; Heng, Li (Penerbit Universiti Kebangsaan Malaysia, 2022)
Auditing services are active throughout corporate takeover process. Audit issues not only affect the nature, efficiency and consequences of takeovers, but also matter the quality and social effects of corporate development after the successful reorganization. This paper aims to enhance the audit quality in the takeover process, and further improve the structure, productivity and social responsibility of takeover parties. Qualitative analysis method and case study are adopted in this paper to investigate the legal issues on audit involved in the takeover process, and explores their fundamental reasons and negative effects on the development of companies and society. This paper finds that since the acquiring companies need to master the comprehensive information of target companies, they incline to choose the audit firms associated with the target companies. Those firms have the opportunity to collude with the target companies and may damage the takeover performance by hiding decision-making power or even falsifying financial data1. In addition, in order to defeat other potential competitors, acquiring companies need to review the financial records and assess the key personnel of target companies within a limited time. They may miss out some technical issues of corporate governance at the stage of pre-takeover due diligence.2 Therefore, this paper suggests that takeover parties adopt shared audit. As the information intermediary, shared audit could effectively eliminate the illegal acts caused by the collusion among auditors and auditees, convey accurate information and promote higher-quality takeovers.